1989
DOI: 10.1093/eurheartj/10.suppl_h.104
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial ischaemia and cardiogenic shock after percutaneous transluminal coronary angioplasty; risk factors for and results of emergency coronary bypass

Abstract: Between 1 September, 1980 and 1 January, 1989, 4142 patients underwent percutaneous transluminal coronary angioplasty (PTCA). We retrospectively studied the 155 [3.7%; 119 males, mean age 53.4 years, (range 33-78 years) and 36 females, mean age 59.6 years (range 40-74 years)] who required urgent coronary artery bypass grafting (CABG) (Group I) and a select control group of 155 patients, in whom PTCA was performed without complications (Group II). Before PTCA, 14 Group I and 42 Group II patients had angina Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several large studies from the mid 1980s to early 1990s have reported perioperative Q-wave myocardial infarction in 21% to 57% of patients and in-hospital mortality ranging from 3% to 19%. [2][3][4][5][6][7][8][9] In the stent era, in-hospital complications after emergency CABG have remained high. In the study by Shubrooks et al, 11 mortality and nonfatal Q-wave myocardial infarctions occurred in 29% and 14% of the cases, respectively, in 1997.…”
Section: Seshadri Et Al Emergency Coronary Bypass Surgery In the Presmentioning
confidence: 99%
See 1 more Smart Citation
“…Several large studies from the mid 1980s to early 1990s have reported perioperative Q-wave myocardial infarction in 21% to 57% of patients and in-hospital mortality ranging from 3% to 19%. [2][3][4][5][6][7][8][9] In the stent era, in-hospital complications after emergency CABG have remained high. In the study by Shubrooks et al, 11 mortality and nonfatal Q-wave myocardial infarctions occurred in 29% and 14% of the cases, respectively, in 1997.…”
Section: Seshadri Et Al Emergency Coronary Bypass Surgery In the Presmentioning
confidence: 99%
“…2 Despite this, emergency coronary artery bypass surgery (CABG) is still associated with a significant in-hospital morbidity and mortality. [2][3][4][5][6][7][8][9] We sought to determine the prevalence, indications, predictors, and in-hospital complications of emergency CABG after PCIs in the stent era.…”
mentioning
confidence: 99%
“…The majority of trials dealing with emergency coronary surgery after PCI were a reaction to the increasing number of PCIs performed in the late 80's. Considering the widespread use of aspirin, clopidogrel, heparin and GPIIb/IIIa inhibitors these trials do not represent the present situation [11,12] with regard to the incidence of complications due to bleeding. In the last 20 years the rate of emergency surgical revascularization dropped from 2 -4 % to 0.5 -2 % [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…After failed PTCA emergency CABG has been associated with Q wave myocardial infarction (QWMI) in the range from 20-50% and mortality from 2-15%. 11,[15][16][17][18][19] In fact, by the late 1980s, the use of percutaneous redilatation and perfusion balloons has reduced the rate of emergency CABG. The 1985-6 National Heart, Lung and Blood Institute Registry showed a reduction in overall emergency CABG from 5.8% to 3.5%."…”
Section: Discussionmentioning
confidence: 99%